PELAKSANAAN JAMINAN SOSIAL TENAGA KERJA BIDANG KECELAKAN KERJA PADA PT. ASTRA INTERNASIONAL/TOYOTA SALE OPERATION AUTO 2000 CABANG DENPASAR - Garjitha, I Putu Gede; Retno Murni, R. A. (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 08, September 2013)
Effectiveness of the implementation of the social security field accident at PT. Astra International / Operation Auto 2000 Toyota Sale Branch Denpasar. Therefore, this paper describes whether the implementation of social security field accident at PT. Astra International / Operation Auto 2000 Toyota Sale Branch Denpasar?, And the factors that affect the implementation of the social security field accident at PT. Astra International / Operation Auto 2000 Toyota Sale Branch Denpasar?. The method used in this paper, the empirical method is descriptive. Based on the results of research done shows that the implementation of social security programs in the field of occupational accidents PT. Astra International Branch Denpasar is effective and in accordance with Regulation Legislation which applies the Law No. 3 of 1992 on Employees' Social Security. Factors affecting the implementation of Social Security on PT. Astra International Branch Denpasar internal factors such as the level of education and awareness of the law, where there is also external factors ie socio-cultural and economic factors.
Keywords: Implementation, Social Security, Manpower, Occupational Accidents